Prebiotics, probiotics and symbiotics and their relationship with colorretal cancer (Research, Society and Development, 2019)
Objective: To identify based on the scientific literature the effects on the use of probiotics and symbiotics in the treatment of colorectal cancer (RCC). Method: This is an integrative review study, conducted in February 2019, with the theme focused on the use of probiotics and symbiotics in RCC. To guide the study the following question was asked: “What is the influence of the use of probiotics or symbiotics in individuals with colorectal cancer?” To survey the articles in the literature, we searched the following databases: LILACS, Medline, Scielo and Pubmed. The following keywords were used to search for the articles: 'Colorectal Neoplasms', 'Probiotics', 'Synbiotics' and 'Nutrition', both used alone or in combinations in Portuguese and English. Results: RCC is the third most common type in the world and has a multifactorial etiology involving heredity, chronic inflammatory diseases, age, diet, obesity, physical inactivity and other factors. The treatment is still associated with a high risk of complications and the use of immunomodulatory diets with the use of probiotics or symbiotics represents a new therapeutic option and its function is to act in prevention and to be allied to the treatment of RCC, becoming of great importance. for the quantitative and qualitative balance of the intestinal microbiota for human health and their importance as adjuvants in the prevention and treatment of colorectal cancer. Conclusion: Probiotic or symbiotic administration is effective for intestinal health, preserving and stimulating beneficial bacteria, promoting intestinal health and decreasing inflammatory activity and the risk of infections after surgical resections.